A novel design of a parallel gripper actuated by a large-stroke shape memory alloy actuator. (August 2019) - Lu, Yifan; Xie, Zhijie; Wang, Jian; Yue, Honghao; Wu, Miao; Liu, Yiwei
Highlights: A novel SMA actuated gripper of large capture range for space application is designed and fabricated. A bias element selection model is developed to achieve the best driving performance of the SMA actuator. An analytical model is established in order to evaluate the capture range of the SMA gripper. A theoretical model is proposed to estimate the grasping force of the SMA gripper for different capturing targets. Abstract: Current traditional robotic grippers for on-orbit capture missions have several disadvantages: large volume and weight, huge energy consumption and high cost. To overcome these problems, a novel design of parallel gripper actuated by a large-stroke shape memory alloy (SMA) actuator is proposed in this paper. The mechanical design of the gripper is presented and each component is expounded in details. Multiple SMA wires are connected in series to achieve a larger stroke of the actuator. A light-weight, small-volume cross-shear hinge coupler is designed to ensure the symmetry and synchronism of the movement of the two gripping arms. In order to evaluate the working performance of the proposed SMA gripper, three theoretical models are developed for bias element selection, gripping force calculation and capture range analysis. A prototype of the gripper is fabricated and a series of experiments are conducted. The actuation characteristics under different bias forces and different currents are tested. The relationship between the gripping force and the sizes of targets are compared. The experimental observations are in good agreement with the theoretical results which demonstrates the correctness of the proposed models. Research results indicate that the proposed SMA gripper can grasp targets reliably and adaptively.